Brachypodium: 20 years as a grass biology model system; the way forward?. (October 2022) - Hasterok, Robert; Catalan, Pilar; Hazen, Samuel P.; Roulin, Anne C.; Vogel, John P.; Wang, Kai; Mur, Luis A.J.
Abstract : It has been 20 years since Brachypodium distachyon was suggested as a model grass species, but ongoing research now encompasses the entire genus. Extensive Brachypodium genome sequencing programmes have provided resources to explore the determinants and drivers of population diversity. This has been accompanied by cytomolecular studies to make Brachypodium a platform to investigate speciation, polyploidisation, perenniality, and various aspects of chromosome and interphase nucleus organisation. The value of Brachypodium as a functional genomic platform has been underscored by the identification of key genes for development, biotic and abiotic stress, and cell wall structure and function. While Brachypodium is relevant to the biofuel industry, its impact goes far beyond that as an intriguing model to study climate change and combinatorial stress. Highlights: Brachypodium offers a unique combination of biological, ecological, phylogenetic, and cytological features. Many features of this model genus depend on its nondomesticated status. These features are combined by well-developed resources such as diverse germplasm collections, sequenced genomes and pangenomes, and extensive mutant collections. Brachypodium provides a solid foundation for diverse research on plant biodiversity, speciation, genome organisation at the cytomolecular level, cell wall organisation, response to abiotic and microbial interactions, including beneficial associations. These features are relevant to understanding ecological responses to environmental change. Thus, despite improvements in genomic sequencing technologies and gene editing technologies in large-genome cereals, Brachypodium retains its value as a model nondomesticated grass genus.